Die Wallacher Deichschau im Jahre 1580.: Zum Quellenwert frühneuzeitlicher Vermessungshandrisse und Karten - Aymans, Gerhard (ERDKUNDE, 1995)
In mediaeval Europe land surveyors used to register the names of landowners and leaseholders together with the size of the allotments they owned or worked in lists which normally had the form of paper rolls (landroll, dikeroll). From the middle of the 16th century onwards these written maps were gradually superseded by hand drawn maps which contained in a sketchy way, apart from topographic illustrations (houses, trees, roads etc.), the outlines of the allotments to be registered and, written into every allotment, the traditional information on ownership, lease holding and size of the area. In the Rhinelands alone many thousands of such sketchy maps have been preserved, but they have rarely been used for historical studies, because they are regarded as unreliable. This paper discusses the reliability of early allotment maps by scrutinizing the survey results of Heinrich von Senheim, the chief surveyor of the Duke of Cleves, in 1580. Senheim surveyed the diked lands of Wallach on the Lower Rhine (north of Duisburg) during the summer of 1580, and jotted down his results in sketch books which were used by generations of successors, both surveyors and map makers, until the very end of the 18th century. Obviously, the later surveyors did not find any fault with the results of the old survey, for they used them again and again. A critical investigation of Meettbuick C, the only one of the survey sketch books of Heinrich von Senheim preserved, shows that there are two answers to the reliability question. The form of the depicted objects is not reliable at all. The allotments have no true scale, and the angles formed by their boundaries do not prove right either. Everything seems to be distorted. On the other hand the measured size, numerically entered in every parcel, turns out to be very reliable indeed. Meettbuick C shows that the surveyor obtained his results by employing trigonometry. He divided all parcels into rectangular triangles which he measured with the help of the geographic quadrant and calibrated measuring rods or chains. The many auxiliary stretches noted in the sketch book, besides the calculated size of every lot, make it possible to remeasure the allotments of 1580 even today, and to reconstruct the whole area in a map which is not only reliable with regard to the size of the depicted allotments - like the original sketch map but also with regard to their form - unlike the original sketch map. The difficulty in finding the unknown form of an allotment known only by its size can be overcome with the help of the cadastral map of 1821 (or any other cadastral maps of the early 19th century). These maps are superior to present day maps - for the purpose - because of the number of changes that have taken place between the original survey (1580) and 1821 are much smaller than those between 1821 and the present day. The result of a reconstruction along the lines discussed above is presented in the form of a map (1: 10,000) of the land use in the diked lands of Wallach in 1580.